Social context and transferable skill development in experiential learning. Issue 4 (4th July 2022) - Collins-Nelsen, Rebecca; Koziarz, Frank; Levinson, Beth; Allard, Erin; Verkoeyen, Stephanie; Raha, Sandeep
ABSTRACT: Increasingly, employers are seeking candidates with transferable skills in addition to technical and educational requirements. Thus, university students seek opportunities to develop transferrable skills, often through extra and co-curricular programs. With this in mind, our research explores student assessments of their own development of transferable skills after participation in a co-curricular, experiential volunteer program (McMaster Children and Youth University) in Canada. Using pre/post-survey methods, we find statistically significant increases in participants' self-assessments of leadership, problem solving, knowledge translation, and knowledge mobilization. Adaptability emerges as an unexpected skill several participants report developing as a result of working with young people. We conclude that co-curricular programs play an important role in transferable skill development. Further, we argue that social contexts of experiential learning opportunities play a significant role in shaping transferrable skill development.